2015
DOI: 10.1186/s12968-015-0141-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of motion correction on reproducibility and spatial variability of quantitative myocardial T2 mapping

Abstract: BackgroundTo evaluate and quantify the impact of a novel image-based motion correction technique in myocardial T2 mapping in terms of measurement reproducibility and spatial variability.MethodsTwelve healthy adult subjects were imaged using breath-hold (BH), free breathing (FB), and free breathing with respiratory navigator gating (FB + NAV) myocardial T2 mapping sequences. Fifty patients referred for clinical CMR were imaged using the FB + NAV sequence. All sequences used a T2 prepared (T2prep) steady-state f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Involuntary participant movement or muscle spasms during MRI data acquisition is often the result of peripheral neuromuscular simulation as oscillating magnetic field gradients can stimulate the peripheral nervous system and cause involuntary muscle spasms in healthy adults [ 68 , 69 ]. Therefore, if involuntary movement persists following additional attempts, researchers should determine the appropriate imaging correction techniques to remove motion artifacts [ 70 , 71 ]. Some may also consider the study’s modest weight loss (−3.3%) as a limitation, potentially confounding results.…”
Section: Discussionmentioning
confidence: 99%
“…Involuntary participant movement or muscle spasms during MRI data acquisition is often the result of peripheral neuromuscular simulation as oscillating magnetic field gradients can stimulate the peripheral nervous system and cause involuntary muscle spasms in healthy adults [ 68 , 69 ]. Therefore, if involuntary movement persists following additional attempts, researchers should determine the appropriate imaging correction techniques to remove motion artifacts [ 70 , 71 ]. Some may also consider the study’s modest weight loss (−3.3%) as a limitation, potentially confounding results.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional myocardial T 1 mapping methods acquire only a single slice per breathhold, necessitating rest periods between subsequent breath-holds, leading to patient discomfort and long scan times. Furthermore, repeated breath-holds may compromise image registration (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…16 Breath-holding problems are well documented in adults and it is likely they are more of an issue in children. 17 These problems include an inability to understand and follow instructions for breath-holding, an inability to maintain the breathhold for the whole scan (15-20 seconds) and fear of the procedure. 16 Few studies have been reported on the use of MRI T2* in children and it appears that most centres either use sedation or general anaesthesia for the procedure.…”
Section: Discussionmentioning
confidence: 99%